A comparison between the impacts of lecturing and flipped classrooms in virtual learning on triage nurses' knowledge and professional capability: an experimental study - Mostafa Javadi; Majid Gheshlaghi; Mostafa Bijani (BMC, 2023)
Abstract Background The quality of triage in emergency department depends on regular evaluation of triage nurses' professional capabilities and development of programs to improve them. Flipped classrooms are a new approach to learning which can be employed to improve professional capabilities. The present study aims to compare the impact of lecturing to flipped classrooms in virtual learning on the knowledge and professional capabilities of triage nurses in the emergency departments of the state hospitals of Yazd province in south-western Iran in 2022. Methods The present study is an experimental work of research. Seventy-four triage nurses participated in the study. Seventy-four triage nurses were randomly allocated to the two groups, including flipped classrooms (group B) and lecturing (group A). The data collection instruments were an emergency department triage nurses' professional capability questionnaire and a triage knowledge questionnaire. The collected data were analyzed in SPSS v.22 using independent t-test, chi-squared test, and repeated measures analysis of variance. Level of significance was set at p ≥ 0.05. Results The participants' mean age was 33.1 ± 4.3 years. As measured one month after the education, the triage knowledge mean score of the nurses who were educated using the flipped classroom method (9.29 ± 1.73) was higher than that of the nurses who were educated via lecturing (8.45 ± 1.788), and the difference was statistically significant (p = 0.001). Also, measured one month after the education, the professional capability mean score of the nurses who were educated using the flipped classroom method (140.27 ± 11.744) was higher than that of the nurses who were educated via lecturing (132.84 ± 10.817), and the difference was statistically significant (p = 0.006). Conclusion There was a significant difference between the pretest and posttest knowledge and professional capability mean scores of both groups immediately after the education. However, measured one month after the education, the mean and standard deviation of the knowledge and professional capability scores of the triage nurses who had been educated via flipped classrooms were higher than those of the nurses in the lecturing group. Thus, virtual learning using flipped classrooms is more effective than lecturing in improving triage nurses' knowledge and professional capability in the long run.